Strategies for Mitigating Negative Impacts of Child Labor Abstract - Serrano Guzmán, Maria Fernanda; Serrano Guzmán, Monica Natalia; Mesa Rivera, Marisol; Marmol Rios, Marina del Mar (DIXI, 2015)
The economic situation in certain regions of Colombia encourages child labor to support the family productive chain. Most studies that have been made present the statistics found at the urban level, so that the rural situation is lef out of indicators in that respect. However, one particular study undertaken in a rural community in Santander (Colombia) showed that child labor performed by children and young people is having an effct on school performance and dropout rates throughout life. Based on the results of this study, strategies were designed to minimize the effcts of child labor. As a result, initiatives are presented that could be made available to the academic community and society in order to mitigate negative impacts stemming from child labor. Additionally, the need for academia to make adjustments in curricula through the incorporation of new pedagogical strategies using learning based on problems, collaborative work and the creation of open programs and learning at a distance is proposed. Sensitization workshops are also proposed for society.
Keywords: learning; education; pedagogical strategy; child labor